Legitimising governance through vocational roles: A conceptual metaphor analysis of budget speeches - Rashid Ali, Farrah Diebaa; Awab, Su'ad (Springer, 2023)
Although on opposing political spectrums, Barisan Nasional (BN) and Pakatan Harapan (PH) legitimised their presence through several vocational roles. These roles were not overtly mentioned, but their use can be unveiled by a conceptual metaphor analysis. This chapter analyses eleven supply bills or better known to Malaysians as budget speeches presented by two Ministers of Finance, Najib Razak (2010–2018) from BN and Lim Guan Eng (2019–2020) from PH. The analysis was informed by conceptual metaphor theory (Lakoff and Johnson, 1980) and membership categorisation analysis (Sacks, 1995). Whilst BN constructed 39 vocational roles for itself, PH had 16 roles. The two coalitions share a preference for certain roles, such as GOVERNMENT IS GENERAL/SOLDIER and GOVERNMENT IS DOCTOR, but BN also favours GOVERNMENT IS CAPTAIN. Both BN and PH legitimise their governance by representing themselves as hero-like-authoritative figures who can handle multiple vocational roles. These roles are played out in narratives highlighting the government’s authority, value systems and ideologies.